Evaluation of the applicability of polymerase chain reaction (PCR) to sex identification in Eurasian blackbirds (Turdus merula) - Dybus, Andrzej; Siemierz, Anna; Wysocki, Dariusz; Szatkowska, Iwona; Muszyńska, Magdalena; Guenzel, Sebastian (Biological Letters, 2010)
Turdus merula is one of most common bird species in Europe. This study verified a method for its sex identification by PCR with P2/P8 primers, based on the CHD1 gene polymorphism, proposed in earlier studies as a universal tool for sex identification in most bird species. Although there are some reports that PCR cannot determine sex in Eurasian blackbirds due to a lack of differences in intron lengths of CHD1-Z and CHD1-W genes, our study showed that such a possibility does exist, so it can contribute to an increased understanding of the biology of this species.